Ontology Design and Workspace Analysis of Large Complex Component Processing Robots - Qin Zhe; Song Xiaohui; Tu Wenbin (Jixie chuandong)
Large complex components are the core structural components of equipment in the fields of aerospace, energy, ships, etc. Such components have large sizes, complex shapes, and high processing accuracy requirements. Nowadays, robotized processing systems can overcome the shortcomings of high cost, poor flexibility of the gantry equipment, which have become a powerful tool for processing large complex components. However, the ontology performance of the existing robotized processing system still has problems such as small workspace and weak load capacity, so a hybrid mechanism that can be used as the core ontology of a large complex component processing robot is proposed in this study. The hybrid mechanism consists of a series of manipulators for processing tasks and a 6-UPS parallel mechanism. The 6-UPS parallel mechanism, driven by six drive rods, is used to support the series manipulator and regulate its position and pose on the one hand, and drive the robot to travel with the hybrid mechanism as the ontology on the other hand. The kinematics modeling and workspace solutions of the serial manipulator, 6-UPS parallel mechanism and the whole hybrid mechanism are completed in this study and it is proved that the workspace of the whole hybrid mechanism is significantly larger than that of the serial manipulator and the 6-UPS parallel mechanism. The virtual prototype of the robot is designed with the proposed hybrid mechanism as the robot ontology. By realizing the gait walking of the virtual prototype in a three-dimensional software, it is proved that the designed robot can further expand the workspace using a walking function.